A SFEM-based evaluation of mode-I Stress Intensity Factor in composite structures. (10th June 2016) - Fantuzzi, Nicholas; Dimitri, Rossana; Tornabene, Francesco
Abstract: The Strong Formulation Finite Element Method (SFEM) based on the Generalized Differential Quadrature (GDQ) method is applied in the present work to estimate numerically the Stress Intensity Factor (SIF) for a single edge-notched tensile specimen (SENT) with different length-to-width ratios and composite materials, as well as for a Center Cracked Tension (CCT) and a Double Edge-Notched Tensile (DENT) specimens, under a mode-I loading condition. The basis notions of the fracture mechanics are herein analyzed numerically in order to evaluate the influence of possible cracks within materials and to relate the dimensions of cracks and the applied loading to the varying stress distribution. The numerical results, in terms of stresses and SIFs, are straightforwardly compared to those ones given by the standard Finite Element Method (FEM) and theoretical predictions available from the literature. This work presents a consistent approach for the computation of the SIF using a strong form methodology. The main aim is to demonstrate the accuracy and efficiency of the proposed methodology when treating classical plane stress problems with cracks. We show and discuss results from several numerical examples, including different composite materials and varying geometries for a mode-I SENT, CCT and DENT specimens.